The potential of supplementing compound organic trace elements at lower levels in Chinese yellow-feathered broiler diets, Part I: Impacts on plasma biochemical parameters, antioxidant capacity, carcass traits, meat quality, and tissue mineral deposition - Xiaoyan Nie; Yucheng Yin; Qi Lu; Fei Zhao; Yang Dai; Rui Wang; Yiwen Ji; Huihua Zhang; Cui Zhu (Poultry Science)
This study was conducted to evaluate the effects of replacing inorganic trace minerals (ITM) with compound organic trace minerals (OTM) at lower levels on plasma biochemical parameters, antioxidant capacity, carcass traits, meat quality, and tissue mineral deposition in Chinese yellow-feathered broilers. A total of 960 one-day-old male broilers were randomly allocated to six treatment groups. The birds were fed with either the basal diets (negative control, NC), or diets supplemented with 1,000 mg/kg (positive control, PC), 300 mg/kg, and 500 mg/kg ITM or OTM for 53 d, respectively. The results showed that the alkaline phosphatase (ALP) activity of the OTM300 group was significantly higher than that of the NC, PC, and ITM300 groups (P < 0.05). Dietary OTM supplementation could significantly increase the serum concentrations of Fe and Cu, promote the deposition of Zn and Cu in breast muscle, and increase Zn content in the tibia of Chinese yellow-feathered broilers (P < 0.05). Furthermore, dietary OTM300 treatment could significantly increase plasma CAT and CuZn-SOD activities, as well as the CAT activity in the liver (P < 0.05). The liver GSH-Px activity of the OTM500 group were significantly higher than the other groups (P < 0.05). Moreover, the supplementation of dietary OTM could significantly increase the pH45min of breast muscle, as well as decrease drip loss24h and drip loss48h of Chinese yellow-feathered broilers (P < 0.05). Furthermore, pH45min was positively correlated with liver T-AOC activity and the concentrations of Zn, Fe, Cu, and Mn in breast muscle, while drip loss48h was negatively correlated with liver T-AOC activity, plasma CAT and CuZn-SOD, as well as the concentration of Cu and Zn in breast muscle. Trace mineral sources or levels had no significant effect on the carcass traits of Chinese yellow-feathered broilers (P > 0.05). Compared with the ITM groups, OTM300 significantly increased the heart index of Chinese yellow-feathered broilers (P < 0.05). Dietary OTM upregulated the mRNA expression of TGF-β and downregulated the mRNA expression of IL-1β in the spleen (P < 0.05). In conclusion, dietary supplementation with compound OTM at lower levels could promote the deposition of trace minerals in serum and tissues, enhance antioxidant capacity, and improve the meat quality of Chinese yellow-feathered broilers.